Compartment Ratio–Integrated Routing Optimization in Small-Fleet Multi-Compartment Distribution of Perishable Food - Effendi, Usman; Angriawan, Rinaldi Dwi; Mulyarto, Aunur Rofiq (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractThe distribution of perishable food products faces challenges related to distance efficiency, cost efficiency, and vehicle capacity utilization, particularly when small fleets must serve multi-product demand while maintaining product quality sensitive to travel time. Vehicle capacity constraints strengthen the relationship between customer visit sequencing and internal vehicle load allocation. This study proposed a Multi-Compartment Vehicle Routing Problem (MCVRP) optimization approach that integrates compartment ratio design and route formation for the distribution of two packaged mozzarella cheese products to 18 customers in a single-depot system. The objective was to minimize total travel distance and evaluate the financial impact through fuel and labor cost components. A deterministic model with two vehicles of 100 kg capacity was formulated and solved using the Ant Colony Optimization algorithm, followed by a separate evaluation of operational costs for direct managerial interpretation. The results show that a 65:140 compartment ratio provides the best configuration, reducing total distance from 119.50 km to 106.20 km, decreasing routes from six to five, and lowering distribution costs by 15.87% per cycle. Capacity utilization improved without adding vehicles, enhancing both operational and financial efficiency. Industrial implications point to scale-up opportunities and enhanced sustainability through energy efficiency in small-scale food distribution.Keywords: Ant Colony Optimization, small fleet, perishable food distribution, Multi-Compartment Vehicle Routing Problem, compartment ratio AbstrakDistribusi produk pangan mudah rusak menghadapi tantangan efisiensi jarak, biaya, dan pemanfaatan kapasitas ketika armada kecil harus melayani permintaan multi-produk dan mutu produk sensitif terhadap waktu tempuh. Keterbatasan kapasitas kendaraan memperkuat keterkaitan antara keputusan urutan kunjungan pelanggan dan pembagian muatan internal kendaraan. Penelitian ini mengusulkan pendekatan optimasi berbasis Multi-Compartment Vehicle Routing Problem yang mengintegrasikan desain rasio kompartemen dan pembentukan rute pada distribusi keju mozzarella 2 varian kemasan kepada 18 pelanggan dalam sistem satu depot. Tujuan penelitian ialah menurunkan jarak tempuh total dan menilai dampak finansial melalui komponen biaya bahan bakar dan tenaga kerja. Metode penelitian memformulasikan model deterministik satu depot dengan dua kendaraan berkapasitas 100 kg, menyelesaikannya menggunakan Ant Colony Optimization lalu mengevaluasi biaya operasional secara terpisah agar interpretasi manajerial lebih langsung. Hasil menunjukkan rasio kompartemen 65:140 sebagai konfigurasi terbaik, menurunkan jarak dari 119,50 km menjadi 106,20 km, mengurangi jumlah rute dari 6 menjadi 5, serta menekan biaya distribusi 15,87% per siklus. Utilisasi kapasitas meningkat tanpa penambahan kendaraan sehingga efisiensi teknis dan finansial membaik secara simultan. Implikasi industri mengarah pada peluang scale-up dan penguatan keberlanjutan melalui efisiensi energi pada distribusi pangan skala kecil.Keywords: Ant Colony Optimization, armada kecil, distribusi pangan mudah rusak, Multi-Compartment Vehicle Routing Problem, rasio kompartemen